Markets with Technological Progress: Pricing, Quality and Novelty - Ludwig von Auer; Mark Trede (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
New and old products differ in two respects: quality and newness. Whereas a higher quality of a new product always benefits consumers, the newness itself benefits some consumers, but not others, and for some, it is even a disadvantage. We capture these features in a Hotelling model of Over- Lapping Innovators (HOLI model), entailing a sequence of static Hotelling games of horizontal product differentiation (newness), that we extend by vertical product differentiation (quality). In this model the firms compete on quality and price. Using advanced dynamic hedonic regression methods, we empirically investigate the actual pricing of firms in the German laser printer market. We show that their pricing corresponds to our model with the entrant acting as the Stackelberg follower.
Keywords: L11; L63; C23; 330